2020
DOI: 10.1002/ejoc.201901821
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Assisted Selenylative Intramolecular Dearomative Carbo‐Spirocyclisation (IDCS) of Homologated‐Ynones

Abstract: A visible light assisted dearomative selenylative carbo‐spirocyclisation of aromatic homologated‐ynones has been reported. The ynones deliver selenylative spiro‐cyclohexadienones and spiro‐diepoxides at varied temperatures. The prescribed methodology is photo‐catalyst free and scalable. The combination of visible light, molecular oxygen and the products synthesized delivers a uniqueness to the designed methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…The development of visible light assisted selenylative spirocyclization reactions of ynones was described by Sarkar and co‐workers [63] . In this study, 1,4‐diarylbut‐3‐yn‐2‐ones reacted with diaryl diselenies under visible light and O 2 at 18 °C to afford a series of seleno‐spirocyclohexadienones 76 in 70–88 % yields.…”
Section: Synthesis Of Carbo‐ and Heterocycles Via Reactions Of Alkynes With Organyl Chalcogenidesmentioning
confidence: 88%
See 1 more Smart Citation
“…The development of visible light assisted selenylative spirocyclization reactions of ynones was described by Sarkar and co‐workers [63] . In this study, 1,4‐diarylbut‐3‐yn‐2‐ones reacted with diaryl diselenies under visible light and O 2 at 18 °C to afford a series of seleno‐spirocyclohexadienones 76 in 70–88 % yields.…”
Section: Synthesis Of Carbo‐ and Heterocycles Via Reactions Of Alkynes With Organyl Chalcogenidesmentioning
confidence: 88%
“…The development of visible light assisted selenylative spirocyclization reactions of ynones was described by Sarkar and co-workers. [63] In this study, 1,4-diarylbut-3-yn-2-ones reacted with diaryl diselenies under visible light and O 2 at 18 °C to afford a series of seleno-spirocyclohexadienones 76 in 70-88 % yields. When the ynones were reacted at 32 °C under standard conditions, a concomitant stereoselective transformation took place and structurally complex seleno-spirodiepoxides 77 were isolated in moderate yields (Scheme 51).…”
Section: Reactions Of Alkynes With Organochalcogen Radical Speciesmentioning
confidence: 91%
“…In 2020, Sarkar and co-workers developed an intramolecular selenylative dearomatization reaction of benzene-derived alkynone in the presence of oxygen (Scheme 38b). 76 Interestingly, slightly higher temperature allowed for the generation of selenospiro-diepoxide as a minor product. The mechanism proposed by the authors indicated that diepoxide was achieved via the double epoxidation of the major product enone with the in situ generated benzeneperoxyseleninic acid.…”
Section: Shu-li Youmentioning
confidence: 99%
“…Under an oxidizing atmosphere, the peroxidation of the spiro intermediate 184 generates the peroxide radical specie 185 followed by elimination of the OH radical affords the respective spirocompound 186 (Scheme 45). [72–75] The absence of the formation of bis ‐arylselenyl olefins is related to the faster intramolecular reaction rather than the intermolecular reaction with another selenyl radical.…”
Section: Spirocyclizationmentioning
confidence: 99%
“…The transformation of ynones 182 into spiro‐cyclohexadienones 186 through reaction with selenium radical species has been performed under similar conditions [74] . The methodology is photocatalyst free and molecular oxygen is employed as the oxidant.…”
Section: Spirocyclizationmentioning
confidence: 99%